2008
DOI: 10.1088/0953-4075/41/2/025501
|View full text |Cite
|
Sign up to set email alerts
|

A macroscopical entangled coherent state generator in a V configuration atom system

Abstract: In this paper, we propose a scheme to produce pure and macroscopical entangled coherent state. When a three-level "V" configuration atom interacts with a doubly reasonant cavity, under the strong classical driven condition, entangled coherent state can be generated from vacuum fields. An analytical solution for this system under the presence of cavity losses is also given.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Thus, for I 2 < I 3 only a small change of a few percent can be observed in the slope of Re(ρ 03 ). In conclusion, we have observed that when the B field takes on values in the range established by the boundary conditions (10) and (11), there is no significant change in the transit time from the normal dispersive region to EIT region (see Section IV C), or in the width EIT from Section IV D.…”
Section: F Variation Of Slope For Re(ρ) With the Coupling Fieldmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus, for I 2 < I 3 only a small change of a few percent can be observed in the slope of Re(ρ 03 ). In conclusion, we have observed that when the B field takes on values in the range established by the boundary conditions (10) and (11), there is no significant change in the transit time from the normal dispersive region to EIT region (see Section IV C), or in the width EIT from Section IV D.…”
Section: F Variation Of Slope For Re(ρ) With the Coupling Fieldmentioning
confidence: 66%
“…In recent years, many extensive studies have been devoted to three-level atomic systems, such as the V system [8,10], the system [11], and the ladder system [12], in which two optical fields are used and, due to quantum interference, one of them is slowed down. Recently, the propagation of a weak probe field in various laser-driven four-level atomic systems was investigated [13].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Numerous schemes have been proposed to generate an entangled coherent state. [7][8][9][10][11] The superposition of coherent state has been realized in experiments such as in superconducting Josephson junctions system, [12] cavity QED system, [13] linear optical system. [14] Optomechanical system, by coupling mechanical resonators to the fields of optical cavities, can provide an available device to observe quantum mechanical behaviors of mesoscopic and even macroscopic systems.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, entangled states between individual qubits have been extensively studied where entanglement is carried by discontinuous states. In recent years, continuous-variable (CV) entanglement has attracted much attention [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] because its many advantages [1]. Traditional schemes of generating CV entanglement is based on the parametric down conversion process [20,21].…”
Section: Introductionmentioning
confidence: 99%